Does Access to Credit Improve Productivity? Evidence from Bulgarian Firms - Gatti, Roberta; Love, Inessa (World Bank, Washington, DC, 2012)
Although it is widely accepted that financial development is associated with higher growth, the evidence on the channels through which credit affects growth on the micro-level is scant. Using data from a cross section of Bulgarian firms, the authors estimate the impact of access to credit (as proxied by indicators of whether firms have access to a credit or overdraft facility) on productivity. To overcome potential omitted variable bias of OLS estimates, they use information on firms' past growth to instrument for access to credit. The authors find credit to be positively and strongly associated with total factor productivity. These results are robust to a wide range of robustness checks.